INVESTIGATING THE DETERMINANTS OF EARNINGS RESPONSE COEFFICIENT IN INDUSTRIAL SECTOR: PANEL DATA ANALYSIS - Saragih, Tiara; Widiyati, Dian; Kee, Susanti (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
This study aims to determine the influence of growth opportunity, systematic risk, and earnings persistence on the earnings response coefficient. This research is focused on industrial sector companies on the Indonesia Stock Exchange between 2018 and 2022. This study applied secondary data, namely financial reports. Purposive sampling is implied as a method for data collection. The total sample is 36 companies, generating 180 observations. The analytical method employed in this study was analysis regression using E-Views. The findings reveal that growth opportunity has a significant negative influence on earnings response coefficient. This shows that companies have earnings growth and will increase the opportunity to receive more response from the market. Companies with high growth opportunities often face uncertainty in future earnings due to the inherent risks of new projects or investments. Investors tend to be more cautious or sceptical of their earnings. Additionally, these companies often reinvest their profits into new projects or expansions, which can reduce short-term profit margins and lead to a negative response from investors. High valuations also increase market expectations, so earnings reports that do not meet expectations can trigger disappointment. Companies in the growth stage may not have achieved revenue stability, as opposed to more mature companies which have more stable and predictable revenues, so their reports get a stronger response from investors. Moreover, systematic risk and earnings persistence have no influence on earnings response coefficient respectively. This research contributes to our understanding of how industrial companies manage their earnings response coefficient.